DIPG-55. Increasing the drug-tumor resonance time in DMG murine models significantly extends survival. (3rd June 2022) - Power, Erica; Zhang, Liang; Rechberger, Julian; Oh, Juhee; Elmquist, William; Daniels, David
Abstract: H3K27-altered diffuse midline glioma (DMG) is a uniformly lethal CNS cancer that predominately occurs in children. In the last decade, while studies revealing the molecular underpinnings of the disease have paved the way for novel therapeutic strategies, this tumor remains a death sentence. Our lab and others have identified numerous drugs of high interest for treating this devasting disease, however, every trial has failed to show benefit. Is our failure to translate these laboratory findings due to the fact we have not found the right drugs or treatment regimens yet? Or is this a failure to get the drugs to the tumor? Or is this simply a very bad disease to treat? The answer is likely multifactorial. Our lab, in collaboration with others, have strong data to show that simply getting drugs to the tumor will not result in a positive benefit. Most drugs are rapidly cleared from their target space. Utilizing techniques that increase the drug-tumor resonance time is necessary to translate our basic science findings to our patients. Picking the right drug and the delivery mechanism is not enough for a positive effect. Here, we assessed the efficacy of a previously identified inhibitor, alisertib, delivered by short-term convection-enhanced delivery or a continuous osmotic pump and found that continuous, direct delivery results in a significant increase in survival (p = 0.0002). Furthermore, long-term survivors showed a decreased tumor burden and on-target drug effects. These data support that translation into patients must consider three factors: 1) selection of a potent therapy, 2) selection of the proper delivery method for that therapy, 3) modulation to ensure that the therapy remains in the targeted tissue long enough for desired effect. Keeping these basic tenets at the forefront of development may finally lead to a more effective treatment strategy for this devastating disease